Islam-Based Caring for the Harmony of Life among Moslem Critically Ill Patients - Suhartini Ismail; Urai Hatthakit (Journal of Evidence-Based Care, 2018)
Background: The application of more humanized approaches in the caring process of the Intensive Care Unit (ICU) patients with the aim of improving the quality of care has been given a growing attention However, there are limited studies regarding the Islam-based caring for the Moslem populations in Indonesia. Aim: This study aimed to explore and describe the caring actions employed by nurses to enhance the harmony of critically ill Muslim patients. Method: This study was conducted on 24 nurses working in the ICU for a minimum of 2 years, as well as patients and their families and a physician. An action research approach was used to develop an Islam-based caring model for the ICU patients. The study population was selected through purposive sampling technique. The data were colected using in-depth interviews and three focus group discussions. Results: The analysis of the obtained data resulted in the emergence of two main themes, including outcomes of the caring practice and harmony of the life of Moslem critically ill patients. The caring actions aimed at promoting the harmony of life for the critically ill patients were presented and discussed. Implications for Practice: The findings of this study are valuable for nursing professionals in enhancing the harmony of life for critically ill patients.